2022
DOI: 10.1002/fsn3.2979
|View full text |Cite
|
Sign up to set email alerts
|

The regulatory effects of Pseudostellaria heterophylla polysaccharide on immune function and gut flora in immunosuppressed mice

Abstract: Polysaccharide (PF40) has been recognized as a main bioactive substances inPseudostellaria heterophylla (Miq.). The current study explored the potential protective effects of PF40 on immune system in mice with cyclophosphamide-induced immunosuppression. The mice were intragastric administered PF40 at the dosage of 100, 200 or 400 mg/kg once daily for 30 days, On the 24th and 25th day, the additional intraperitoneal injection of PF40 (50 mg/kg) were administered. The results showed that PF40 enhanced the cell-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 61 publications
2
7
0
Order By: Relevance
“…After intervention with PHD and PHP, the rats with SDS showed a significant increase in immune organ index and decrease in the levels of IL-6, and TNF-α, suggesting that PHD and PHP improved the immune function of SDS rats. Previous research by our group found that a purified polysaccharide from PHP (PF40) could enhance cell-mediated immunity by improving macrophage phagocytosis, splenocyte proliferation, NK cell activity and delayed-type hypersensitivity response 35 . This might be the mechanism for PHD and PHP enhancing immune function.…”
Section: Discussionmentioning
confidence: 95%
“…After intervention with PHD and PHP, the rats with SDS showed a significant increase in immune organ index and decrease in the levels of IL-6, and TNF-α, suggesting that PHD and PHP improved the immune function of SDS rats. Previous research by our group found that a purified polysaccharide from PHP (PF40) could enhance cell-mediated immunity by improving macrophage phagocytosis, splenocyte proliferation, NK cell activity and delayed-type hypersensitivity response 35 . This might be the mechanism for PHD and PHP enhancing immune function.…”
Section: Discussionmentioning
confidence: 95%
“…Modern pharmacological studies showed that P. heterophylla polysaccharides enhanced cell-mediated immunity, lowered blood lipid and blood pressure, and increased hemolysin content in the blood after immunization, and were used in the treatment of diabetes and its complications. 6,24 Heterophyllin B of P. heterophylla can improve mouse memory via neurite regeneration and immunomodulation. 25 Our results showed that P. heterophylla increased the content of white and red blood cells and decreased the content of platelets following cyclophosphamide injury.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] Our results suggest that P. heterophylla alters the diversity and composition of the gut bacterial community, which is consistent with a previous study suggesting that the crude polysaccharides of P. heterophylla effectively regulate gut microbiota. 6 The gut microbiota mainly consists of the phyla Bacteroidetes and Firmicutes, which contain a large number of bacteria producing different types of polysaccharide-degrading enzymes and then degrading polysaccharide carbohydrates to various short-chain fatty acids. 33,34 These short-chain fatty acids can modulate immune responses of the host, regulate epithelial barrier function and provide an energy source for the gut microbiota.…”
Section: Pseudostellaria Heterophylla Mediates the Gut Microbiota And...mentioning
confidence: 99%
See 1 more Smart Citation
“…Chrysanthemum upregulates of antioxidant enzymes and downregulates of NF-κB and some proinflammatory cytokines, such as TNF-α, IL-1β, and IL-6 ( Wu et al, 2014 ). Aucklandia lappa, (gastrointestinal inflammatory diseases ( He et al, 2022 )), Agastache rugosa (antioxidant ( Yeo et al, 2021 ) ) Pseudostellaria heterophylla (immune function ( Kan et al, 2022 )), and Astragalus membranaceus (Antifatigue and Anti-Inflammatory ( Huang et al, 2022 )) are known to have broad-spectrum pharmacological activities. Therefore, according to the theory of TCM and modern Western medical research, treatment with FuXi-Tiandi-Wuxing Decoction might have exhibited beneficial effects on NCP.…”
Section: Discussionmentioning
confidence: 99%